Workfare versus transfers in rural India. (December 2018) - Alik-Lagrange, Arthur; Ravallion, Martin
Highlights: Past assessments of workfare schemes are inconsistent with the policy rationale in poor rural economies. A new evaluation method is implemented for India's National Rural Employment Guarantee Scheme. Targeting performance is good but not enough to compensate for the loss from work requirements. The policy ranking switches in favor of a basic-income guarantee over workfare. Abstract: Prevailing methods for evaluating workfare schemes are inconsistent with the arguments made for workfare in poor rural economies. Those arguments emphasize the existence of higher involuntary underemployment among the poor and the fact that the type of work provided by these schemes gives disutility, deterring non-poor households from participating. To include these features, the consumption-based welfare metric used in past assessments of workfare schemes in underemployed developing countries is generalized to incorporate a welfare loss from casual manual work, while allowing the government to independently value the work done for other reasons. Using data for India's National Rural Employment Guarantee Scheme (NREGS), the paper shows that the policy ranking switches in favor of a basic-income guarantee (BIG) over workfare. Allowing for a welfare loss from casual manual labor implies a more "poor-poor" targeting performance, but this is not sufficient to compensate for the direct welfare loss from the work requirement for plausible parameter values. A BIG dominates NREGS for a given total outlay on workfare wages.